Electrodeposited Iron as a Biocompatible Material for Microneedle Fabrication. Issue 9 (23rd July 2015) - Miller, Philip R.; Boehm, Ryan D.; Skoog, Shelby A.; Edwards, Thayne L.; Rodriguez, Mark; Brozik, Susan; Brener, Igal; Byrd, Thomas; Baca, Justin T.; Ashley, Carlee; Narayan, Roger J.; Polsky, Ronen
Abstract Electroplated iron was investigated as a novel material for microneedle fabrication due to its recent success as a biocompatible metal in other medical device applications. Hollow polymer microneedles were made using a laser direct write process that involved two‐photon polymerization of a commercially available Class 2a biocompatible polymer and subsequent electroplating of this structure with iron. Electroplating bath and deposition conditions were shown to affect the mechanical properties of both iron plated microneedles and iron plated on planar polymer substrates. Conditions for depositing the iron coatings were investigated in terms of grain size, residual strain, and elemental composition for planar iron samples. Fracture strength and puncture mechanics into ex vivo porcine skin for iron coated hollow microneedles were examined. Biocompatibility testing was performed using the MTT assay against human epidermal keratinocytes with several concentrations of iron extract to investigate iron as a material used for transdermal applications. Iron coatings proved to significantly improve the strength of the hollow polymer microneedles and sustained structural integrity up to 7 insertions into porcine skin without bending. A commercially available device (Medtronic MiniMed Quick‐Serter®) was used for controlled application of microneedles into porcine skin and estimations of insertion forces for the device were made. Plating conditions were optimized such that an adherent, uniform, and high purity iron coating was deposited onto polymer substrates and polymer microneedles without delamination or fracturing of the microneedles upon ex vivo insertion into porcine skin.